Experimental Study of a New Metallic Damper Using Hourglass Fuse - Mohammad Hossein Afridoon; Reza Aghayari; Mohammad Hosein Adibrad; Mehrzad Tahamouliroudsari (مهندسی عمران شریف)
Being one of the world’s most earthquake-prone countries, Iran has suffered thousands of lives lost in earthquakes throughout the past decades. The metallic yielding damper is a specific kind of passive structural control device that has shown effective behavior in past earthquakes. In this paper, a new metallic yielding damper made of a number of hourglass shape pins (HSP) for enhancing the seismic behavior of building structures is proposed and has been experimentally evaluated under monotonic and quasi-static cyclic loading. The specimens were subjected to drift levels beyond the expected design ones to identify their complete behavior and all possible failure modes. The main feature of the proposed damper is replaceable hourglass shape pins (HSP) fuse. For this purpose, conventional reinforcing steel bars in construction practice have been shaped by a lathe machine in the form of hourglass pins. These hourglass pins dissipate energy mostly through flexural and tensile mechanisms when subjected to inelastic cyclic deformation and can be replaced easily in case of failure after severe earthquakes. Moreover, this damper is economical, easy to install, and built with no special fabrication technique. The hysteresis behavior and other important parameters of the damper, such as capacity of energy dissipation, effective stiffness, and equivalent damping, and the effect of how the HSP is connected to its supporting plates (welding or connection by utilizing nuts) on these behaviors have been studied through laboratory tests. A simplified analytical procedure using plastic analysis and simple rules of mechanics of solids was found to accurately predict the HSP behavior and was found to be consistent with experimental results. The experimental results indicate that the bars successfully performed their function as energy absorbers and fuses in all specimens, but the way HSP is connected to supporting plates can greatly affect its behavior. In the case of nut connection, a significant amount of pinching was observed in hysteresis loops which is the result of residual displacements between HSP and supporting plates and welding the bars to plates seems to solve this problem, resulting in fat and sustainable hysteresis loop without any significant strength and stiffness degradation and good energy dissipation capacity (with respect to HSP’s low weight) of the purposed damper was reached. Although both types of connections have shown acceptable behavior throughout cyclic loading, total energy absorption capacity and equivalent viscous damping in welded connections in comparison with the nut connection have been improved by 91 and 53 percent, respectively.